Bibliometric analysis of leadership and physical education based on Scopus data - Novri Gazali; Norazlinda Saad (Institute of Advanced Engineering and Science, 2023)
This paper aims to conduct a bibliometric analysis of articles published in the Scopus database on leadership and physical education. The bibliographic data set was administered using VOSviewer. According to the search results, there were a combined 614 articles on leadership and physical education studies. Additionally, the researchers restricted the search to English-language journal articles and the types of documents that may be found. Consequently, 427 articles worth of records were discovered. Based on publications in the Scopus database, the findings revealed that the development of publications in the fields of leadership and physical education has increased, although there is an up-and-down trend from year to year; “quest” became the first choice among other publication media to publish research results; Beauchamp from Canada is the most contributing and influential author on this topic; physical education, physical activity, leadership, curriculum, transformational leadership, adolescents, health, sport, professional development, and education are keywords that frequently feature in those. Therefore, by highlighting specific gaps, a thorough analysis of leadership in physical education might help scholars and practitioners advance current understanding in this field.